Hubungan antara Lumbosacral Transitional Vertebra dan Degenerasi Diskus Lumbal pada Pemeriksaan MRI: Relationship between Lumbosacral Transitional Vertebra and Lumbar Disc Degeneration on MRI Examination - Aulia Ramadhani Simatupang; Laila Syalsabilah Pohan; Putri Salsabilah Ritonga; Anisah Dini Atika; Miftahul Jannah; Nirwana Claudia Br Sitepu; Rifky Audiansyah Pasaribu; Intan Maulina (Elektriese: Jurnal Sains dan Teknologi Elektro, 2026)
Lumbosacral Transitional Vertebra (LSTV) is a congenital anatomical variation at the transition between the last lumbar vertebra and the sacrum that can affect the biomechanics of the lumbosacral spine. These biomechanical changes may increase mechanical stress on the overlying vertebral segments and accelerate lumbar disc degeneration. Lumbosacral disc degeneration is a major cause of low back pain, with high prevalence in the productive-age population and an impact on quality of life and productivity. Magnetic Resonance Imaging (MRI) is an imaging modality with high accuracy for evaluating soft-tissue structures of the spine, thereby playing an important role in identifying LSTV and assessing the degree of disc degeneration. This study used a systematic literature review method to analyze the relationship between LSTV and lumbar disc degeneration based on MRI findings. A literature search was conducted in PubMed, Google Scholar, ScienceDirect, and ResearchGate databases using the keywords "Lumbosacral Transitional Vertebra", "LSTV", "Lumbar Disc Degeneration", and "MRI". The obtained articles were then selected based on predetermined inclusion and exclusion criteria. Of the 252 articles found, 38 met the criteria for further analysis. The review results showed that most studies reported an increased risk of lumbar disc degeneration in individuals with LSTV, particularly in the segments cranial to the transitional vertebrae, such as L4–L5. These findings suggest that LSTV may affect biomechanical load distribution in the lumbosacral spine. Therefore, identifying LSTV via MRI is important in evaluating patients with low back pain to help determine structural risk factors and support more appropriate management planning.